How do apprentices moderate the influence of organizational innovation on the technological innovation process? - Rupietta, Christian [Verfasser]; Meuer, Johannes [Verfasser]; Backes-Gellner, Uschi [Verfasser] (My University, 2021)
“This paper contributes to the literature on non-monetary benefits of Vocational Education and Training (VET) by investigating its influence on a firm’s innovation process. While an increasing number of studies finds positive effects of VET on innovation in firms, the role that apprentices play in this mechanism has largely been unexplored. To analyze this role, we use the distinction between technological and organizational innovation, two complementary forms of innovation. When investigating the initiators of organizational innovation, to date, research has primarily focused on internal and external change agents at upper echelons. We conceptualize apprentices as hybrid (a combination of internal and external) change agents at lower echelons. We examine how apprentices in the Swiss VET system are key to integrating external knowledge (through school-based education) with internal knowledge (through on-the-job training) and moderating the influence of organizational innovation on technological innovation. Drawing on a sample of 1240 firms from a representative Swiss Innovation Survey, we show that apprentices leverage the positive association between innovations in a firm’s business processes and organization of work with incremental innovations. With the description of a new mechanism that shows the significant role of apprentices on firms’ technological innovation activities and evidence for supportive associations between key variables, we contribute to the understanding of the influence of VET on innovation in firms.“ (authors‘ abstract; BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; S 1.3 Berufliche Erstausbildung; 370; 330; Betrieb; Ausbildungsbetrieb; Innovationsfähigkeit; Innovationsprozess; Einflussfaktor; Berufsausbildung; Nutzen; Auszubildender; Organisationsentwicklung; Technische Entwicklung; Schweiz